Identifikasi Faktor-Faktor Pendorong Adopsi Fintech pada UMKM di Priangan Timur - Aquinaldo Sistanto Putra (Universitas Hamzanwadi, 2022)
Fintech, as a part of information technology development, has been utilized by business sectors, including the MSMEs. This research aims to identify the influencing factor of MSMEs from the Eastern Priangan region to use fintech. The theory of planned behavior was selected as the theoretical model for this research. This model has three predictors, namely attitude, subjective norms, and perceived behavioral control. All of these predictors were used as the independent variables. Innovativeness was added as the fourth independent variable. The intention to use fintech is set as the dependent variable. This research used quantitative and verificative approach. The sample size was determined by simple random sampling. A total of 230 MSMEs from the Eastern Priangan region have participated in this research. The data collection process was completed by distributing online questionnaires in Google Forms. The collected data was analyzed with multiple linear regression, followed by hypotheses testing. The results revealed that attitude (t = -,070) and subjective norms (t = 0,968) didn’t have a significant influence on fintech adoption. Perceived behavioral control (t = 2,215) and innovativeness (t=8,685), on the contrary, generated significant influence